Conformal SiO2 coating of sub-100 nm diameter channels of polycarbonate etched ion-track channels by atomic layer deposition - Sobel, Nicolas; Hess, Christian; Lukas, Manuela; Spende, Anne; Stühn, Bernd; Toimil-Molares, M. E.; Trautmann, Christina (Beilstein Journal of Nanotechnology, 2015)
Polycarbonate etched ion-track membranes with about 30 µm long and 50 nm wide cylindrical channels were conformally coated with SiO2 by atomic layer deposition (ALD). The process was performed at 50 °C to avoid thermal damage to the polymer membrane. Analysis of the coated membranes by small angle X-ray scattering (SAXS) reveals a homogeneous, conformal layer of SiO2 in the channels at a deposition rate of 1.7–1.8 Å per ALD cycle. Characterization by infrared and X-ray photoelectron spectroscopy (XPS) confirms the stoichiometric composition of the SiO2 films. Detailed XPS analysis reveals that the mechanism of SiO2 formation is based on subsurface crystal growth. By dissolving the polymer, the silica nanotubes are released from the ion-track membrane. The thickness of the tube wall is well controlled by the ALD process. Because the track-etched channels exhibited diameters in the range of nanometres and lengths in the range of micrometres, cylindrical tubes with an aspect ratio as large as 3000 have been produced.
Keywords: atomic layer deposition (ALD); ion-track technology; nanochannels; polycarbonate; silica (SiO2); small angle X-ray scattering (SAXS); track-etched channels; X-ray photoelectron spectroscopy (XPS)

Nuclear tracks in solids: Principles and applications - Fleisher, R. L.; Price, P. B.; Walker, R. M. (University of California Press, 1975)

Micro- and Nanoengineering with Ion Tracks - Trautmann, C. (Springer, 2009)

(untitled) - Toimil-Molares, M. E. (Beilstein J. Nanotechnol., 2012)

(untitled) - Ferain, E.; Legras, R. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1994)

(untitled) - Apel, P. Yu.; Blonskaya, I. V.; Dmitriev, S. N.; Orelovitch, O. L.; Presz, A.; Sartowska, B. A. (Nanotechnology, 2007)

(untitled) - Cornelius, T. W.; Schiedt, B.; Severin, D.; Pépy, G.; Toulemonde, M.; Apel, P. Yu.; Boesecke, P.; Trautmann, C. (Nanotechnology, 2010)

(untitled) - Mara, A.; Siwy, Z.; Trautmann, C.; Wan, J.; Kamme, F. (Nano Lett., 2004)

(untitled) - Vlassiouk, I.; Kozel, T. R.; Siwy, Z. S. (J. Am. Chem. Soc., 2009)

(untitled) - Ali, M.; Yameen, B.; Neumann, R.; Ensinger, W.; Knoll, W.; Azzaroni, O. (J. Am. Chem. Soc., 2008)

(untitled) - Toimil-Molares, M. E.; Buschmann, V.; Dobrev, D.; Neumann, R.; Scholz, R.; Schuchert, I. U.; Vetter, J. (Adv. Mater., 2001)

(untitled) - Cornelius, T. W.; Brotz, J.; Chtanko, N.; Dobrev, D.; Miehe, G.; Neumann, R.; Toimil Molares, M. E. (Nanotechnology, 2005)

(untitled) - Kohli, P.; Wharton, J. E.; Braide, O.; Martin, C. R. (J. Nanosci. Nanotechnol., 2004)

(untitled) - Muench, F.; Oezaslan, M.; Seidl, T.; Lauterbach, S.; Strasser, P.; Kleebe, H. J.; Ensinger, W. (Appl. Phys. A, 2011)

(untitled) - Lück, H.-B. (Nucl. Instrum. Methods Phys. Res., 1983)

(untitled) - Sparreboom, W.; van den Berg, A.; Eijkel, J. C. T. (Nat. Nanotechnol., 2009)

(untitled) - Schoch, R. B.; Han, J.; Renaud, P. (Rev. Mod. Phys., 2008)

(untitled) - Cornelius, T. W.; Toimil-Molares, M. E.; Karim, S.; Neumann, R. (Phys. Rev. B, 2008)

(untitled) - Canlas, C. P.; Lu, J. L.; Ray, N. A.; Grosso-Giordano, N. A.; Lee, S.; Elam, J. W.; Winans, R. E.; Van Duyne, R. P.; Stair, P. C.; Notestein, J. M. (Nat. Chem., 2012)

(untitled) - Romero, V.; Vega, V.; Garcia, J.; Zierold, R.; Nielsch, K.; Prida, V. M.; Hernando, B.; Benavente, J. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - George, S. M. (Chem. Rev., 2010)

Atomic Layer Deposition on Nanostructured Materials - Elam, J. W. (Coatings on High Aspect Ratio Structures, 2012)

(untitled) - i Codinachs, L. M.; Birkenstock, C.; Garma, T.; Zierold, R.; Bachmann, J.; Nielsch, K.; Schoning, M. J.; i Morral, A. F. (Phys. Status Solidi A, 2009)

(untitled) - Velleman, L.; Triani, G.; Evans, P. J.; Shapter, J. G.; Losic, D. (Microporous Mesoporous Mater., 2009)

(untitled) - Yang, S. Y.; Jeon, G.; Kim, J. K. (J. Mater. Chem., 2012)

(untitled) - Triani, G.; Evans, P. J.; Attard, D. J.; Prince, K. E.; Bartlett, J.; Tan, S.; Burford, R. P. (J. Mater. Chem., 2006)

(untitled) - Bae, C.; Kim, S.; Ahn, B.; Kim, J.; Sung, M. M.; Shin, H. (J. Mater. Chem., 2008)

(untitled) - VanDersarl, J. J.; Xu, A. M.; Melosh, N. A. (Nano Lett., 2012)

(untitled) - Abou Chaaya, A.; Le Poitevin, M.; Cabello-Aguilar, S.; Balme, S.; Bechelany, M.; Kraszewski, S.; Picaud, F.; Cambedouzou, J.; Balanzat, E.; Janot, J.-M.; Thami, T.; Miele, P.; et al. (J. Phys. Chem. C, 2013)

(untitled) - Yang, X.; Tang, H.; Cao, K.; Song, H.; Sheng, W.; Wu, Q. (J. Mater. Chem., 2011)

(untitled) - Sneh, O.; Wise, M. L.; Ott, A. W.; Okada, L. A.; George, S. M. (Surf. Sci., 1995)

(untitled) - Du, Y.; Du, X.; George, S. M. (Thin Solid Films, 2005)

(untitled) - Nottbohm, C. T.; Hess, C. (Catal. Commun., 2012)

(untitled) - Yu, X.-R.; Hantsche, H. (Surf. Interface Anal., 1993)

Practical Surface Analysis - Briggs, D.; Seah, M. P. (John Wiley & Sons, 1990)

(untitled) - Kuttich, B.; Engel, M.; Trautmann, C.; Stühn, B. (Appl. Phys. A, 2014)

(untitled) - Engel, M.; Stühn, B.; Schneider, J. J.; Cornelius, T.; Naumann, M. (Appl. Phys. A, 2009)

(untitled) - Ramola, R. C.; Negi, A.; Semwal, A.; Chandra, S.; Rana, J. M. S.; Sonkawade, R. G.; Kanjilal, D. (J. Appl. Polym. Sci., 2011)

Characterization and chemical modification of the silica surface - Vasant, E. F.; van der Voort, P.; Vrancken, K. C. (Elsevier, 1995)

(untitled) - Alfonsetti, R.; Lozzi, L.; Passacantando, M.; Picozzi, P.; Santucci, S. (Appl. Surf. Sci., 1993)

High Resolution XPS of Organic Polymers - Briggs, D.; Beamson, G. (John Wiley & Sons, 1992)

(untitled) - Wilson, C. A.; Grubbs, R. K.; George, S. M. (Chem. Mater., 2005)